2021
DOI: 10.1016/j.chest.2020.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Disparities in Lung Cancer Incidence for Gender Minority Individuals Using California Cancer Registry Data

Abstract: Gender minority individuals (GMIs) face unique challenges in cancer diagnosis and care. 1,2 Disproportionate burden of lung cancer is expected among GMIs because of their high smoking rate and known disparities in cancer screening. 3 However, population-based cancer registry data have not been fully used in assessing the cancer disparities among GMIs, 1 even though population-based cancer registries do collect sex information beyond male and female. 4 We found one previous study using national cancer surveilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In one study, males who self-identified as gay/lesbian and who had no medical cost burden had higher odds of receiving lung cancer screening, whereas being bisexual was associated with a lower likelihood of screening, suggesting there are sexual-identity disparities in utilizing lung cancer screening ( 94 ). After diagnosis, treatment options for gender minority individuals appeared to have similar proportions of surgical, chemotherapy, and radiation therapies as gender majority ( 95 ). Additionally, one study highlighted that LGB survivors are more likely to participate in cancer clinical trials than heterosexual survivors, but the data were not stratified by cancer type ( 96 ).…”
Section: Ruralmentioning
confidence: 99%
“…In one study, males who self-identified as gay/lesbian and who had no medical cost burden had higher odds of receiving lung cancer screening, whereas being bisexual was associated with a lower likelihood of screening, suggesting there are sexual-identity disparities in utilizing lung cancer screening ( 94 ). After diagnosis, treatment options for gender minority individuals appeared to have similar proportions of surgical, chemotherapy, and radiation therapies as gender majority ( 95 ). Additionally, one study highlighted that LGB survivors are more likely to participate in cancer clinical trials than heterosexual survivors, but the data were not stratified by cancer type ( 96 ).…”
Section: Ruralmentioning
confidence: 99%